2013
DOI: 10.1016/j.ejc.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Crossing number additivity over edge cuts

Abstract: We prove that if G is a graph with an minimal edge cut F of size three and G 1 , G 2 are the two (augmented) components of G − F , then the crossing number of G is equal to the sum of crossing numbers of G 1 and G 2 . Combining with known results, this implies that crossing number is additive over edge-cuts of size d for d ∈ {0, 1, 2, 3}, whereas there are counterexamples for every d ≥ 4. The techniques generalize to show that minor crossing number is additive over edge cuts of arbitrary size, as well as to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Note that any degree 1 wall vertex (of a tile from S) is always identified with another degree 1 wall vertex, resulting in suppression of a degree 2 vertex in the final graph G. Hence the total number of vertices in G equals Proof. An elementary checking yields that the smallest density of a simple tile in T is 3 1 5 , achieved by T a of characteristics (5,16), and the largest is 4, achieved by T c and T d of characteristics (4,16). Lemma 7.1 combined with Theorem 6.2 implies that the average degree r of an infinite family must be in the specified interval.…”
Section: Average Degrees In 2-crossing-critical Familiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Note that any degree 1 wall vertex (of a tile from S) is always identified with another degree 1 wall vertex, resulting in suppression of a degree 2 vertex in the final graph G. Hence the total number of vertices in G equals Proof. An elementary checking yields that the smallest density of a simple tile in T is 3 1 5 , achieved by T a of characteristics (5,16), and the largest is 4, achieved by T c and T d of characteristics (4,16). Lemma 7.1 combined with Theorem 6.2 implies that the average degree r of an infinite family must be in the specified interval.…”
Section: Average Degrees In 2-crossing-critical Familiesmentioning
confidence: 96%
“…Proof. An elementary checking yields that the smallest density of a simple tile in T is 3 1 5 , achieved by T a of characteristics (5,16), and the largest is 4, achieved by T c and T d of characteristics (4,16). Lemma 7.1 combined with Theorem 6.2 implies that the average degree r of an infinite family must be in the specified interval.…”
Section: Average Degrees In 2-crossing-critical Familiesmentioning
confidence: 96%
“…Of these, 4-regular 3-critical graphs were constructed by Pinontoan and Richter [16], and 4-regular c-critical graphs are known for every c ≥ 3, c = 4 [3]. Salazar observed that the arguments of Richter and Thomassen could be applied to average degree as well, showing that an infinite family of c-crossing-critical graphs of average degree d can exist only for d ∈ (3,6], and established their existence for d ∈ [4,6). Nonexistence of such families with d = 6 was established much later by Hernández, Salazar, and Thomas [9], who proved that, for each fixed c, there are only finitely many c-crossing-critical simple graphs of average degree at least six.…”
Section: Introductionmentioning
confidence: 99%